The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1614/ws-d-09-00054.1
|View full text |Cite
|
Sign up to set email alerts
|

Management Filters and Species Traits: Weed Community Assembly in Long-Term Organic and Conventional Systems

Abstract: Community assembly theory provides a useful framework to assess the response of weed communities to agricultural management systems and to improve the predictive power of weed science. Under this framework, weed community assembly is constrained by abiotic and biotic “filters” that act on species traits to determine community composition. We used an assembly approach to investigate the response of weed seed banks to 25 yr of management-related filtering in three different row-crop management systems in southea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 93 publications
10
102
0
Order By: Relevance
“…Compared to no-till conventional fields where crop residues may impede carabid movement; tillage in organic fields may affect the carabid activity positively by reducing crop residues and hence their capture rates could be higher [52]. Bengtsson et al [9] and Ryan et al [53] also found a greater abundance of weed seeds, insect pests and, concomitantly, more carabid beetles in organic systems compared with conventional systems. By contrast, previous studies have suggested that increased soil disturbance due to the fact that tillage in organic fields may reduce ground beetle habitat suitability [47] and bury weed seeds, thereby excluding seed-preying beetles [54], and increasing the beetle larvae and adult mortality [55].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to no-till conventional fields where crop residues may impede carabid movement; tillage in organic fields may affect the carabid activity positively by reducing crop residues and hence their capture rates could be higher [52]. Bengtsson et al [9] and Ryan et al [53] also found a greater abundance of weed seeds, insect pests and, concomitantly, more carabid beetles in organic systems compared with conventional systems. By contrast, previous studies have suggested that increased soil disturbance due to the fact that tillage in organic fields may reduce ground beetle habitat suitability [47] and bury weed seeds, thereby excluding seed-preying beetles [54], and increasing the beetle larvae and adult mortality [55].…”
Section: Discussionmentioning
confidence: 99%
“…Research regarding the effects of ZT on weeds in conventional systems might be used to anticipate consequences of ZT in organic systems for processes such as weed seed distribution within the soil profile. However, other observations from ZT studies that include herbicide applications may need reconsideration when applied to organic systems since herbicide use is such a strong filter on weed community assembly processes [59][60][61]. Likewise, research results from conventional vs. organic tillage studies oftentimes will differ because organic fields tend to have greater weed species density and diversity than fields managed conventionally [6,[62][63][64][65].…”
Section: Organic Zero Tillage Effects On Weedsmentioning
confidence: 99%
“…Conservation tillage also favors the spread of perennial weeds [69,70]. Previous research has demonstrated increases in winter annual weed species in organic systems [60], and increases in troublesome perennial species such as dandelion (Taraxacum officinale Weber) and Canada thistle (Cirsium arvense L.) in organic conservation tillage systems [53,68]. For these reasons, organic ZT systems may be particularly prone to winter annual and perennial weed problems.…”
Section: Organic Zero Tillage Effects On Weedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, viewed within a community assembly framework (sensu Booth and Swanton 2002), tillage is a strong assembly "filter" that can either constrain or advance the membership of species within the subsequent weed community (Ryan et al 2010;Smith 2006).…”
mentioning
confidence: 99%